2019
DOI: 10.1172/jci.insight.125570
|View full text |Cite
|
Sign up to set email alerts
|

MAGI1 as a link between endothelial activation and ER stress drives atherosclerosis

Abstract: Conflict of interest: JT is a cofounder of Principia Biopharma, which has licensed the p90RSK inhibitor FMK-MEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 47 publications
2
54
0
Order By: Relevance
“…The p90 ribosomal S6 kinase (p90RSK) signaling cascade has been demonstrated to play an essential role in multiple cellular functions with the ability to phosphorylate and regulate the activity of many transcriptional factors and kinases. In a previous study, we found that p90RSK directly phosphorylates MAGI1 S741 and causes MAGI1 de-SUMOylation at K931, leading to EC activation (29). In this study, we will examine whether these p90RSK-dependent MAGI1 post-translational modifications (PTMs) impact EC barrier functions.…”
Section: Introductionmentioning
confidence: 98%
“…The p90 ribosomal S6 kinase (p90RSK) signaling cascade has been demonstrated to play an essential role in multiple cellular functions with the ability to phosphorylate and regulate the activity of many transcriptional factors and kinases. In a previous study, we found that p90RSK directly phosphorylates MAGI1 S741 and causes MAGI1 de-SUMOylation at K931, leading to EC activation (29). In this study, we will examine whether these p90RSK-dependent MAGI1 post-translational modifications (PTMs) impact EC barrier functions.…”
Section: Introductionmentioning
confidence: 98%
“…ER stress was chosen because ubiquitin D, encoded by UBD, is involved in the ER stress response, and risk-variant APOL1 appears to localize to the ER membrane 30 . Furthermore, ER stress is becoming an increasingly recognized driver of complex diseases, including CKD [31][32][33][34] . To induce ER stress, we treated organoids with 5 µM tunicamycin for 24 hours and observed increased expression of unfolded protein response genes EDEM1 and HSPA5 by RT-qPCR ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Ocular involvement in sarcoidosis has been highlighted recently in a large GWAS screening identifying seven variants in the MAGI1 (membrane associated guanylate kinase with inverted structure 1) gene, encoding an adaptor protein that stabilizes epithelial and endothelial cell-cell contacts mainly through the PTEN/phosphatidylinositol-3 kinase/Akt and β-catenin pathways [34]. MAGI1 has been related to tumor progression in various cancers and to autoimmune diseases in rat models and in human psoriatic arthritis [80].…”
Section: Other Pathways Identified By Gwas In Sarcoidosis Etiologymentioning
confidence: 99%